Predictors for Short-Term Efficacy of Allergen-Specific Sublingual Immunotherapy in Children with Allergic Rhinitis - Wenlong Liu; Qingxiang Zeng; Renzhong Luo (Mediators of Inflammation)
Background.A good compliance in allergen-specific sublingual immunotherapy (SLIT) often comes from good short-term efficacy. We aimed to evaluate the pretreatment parameters which can predict the short-term clinical efficacy in children that underwent SLIT. Methods. 517 children with allergic rhinitis (AR) that underwent SLIT were recruited in this study. Baseline clinical characteristics and laboratory parameters were collected, and the clinical efficacy was evaluated using symptom and medication scores. A multivariate logistic regression model and receiver operating characteristic (ROC) curves were established. Results. A total of 303 (65%) in 466 children that underwent SLIT achieved short-term clinical efficacy. The time of using the air conditioner was negatively correlated with clinical efficacy, whereas the serum-specific IgE (s-IgE) levels, the serum IL-10 and IL-35 levels, and the s-IgE/total-IgE ratio were positively correlated with clinical efficacy. Conclusion. The time of using the air conditioner, serum-specific IgE (s-IgE) levels, serum IL-10 and IL-35 levels, and s-IgE/total-IgE ratio may be helpful for child selection before SLIT.